Da espiral de violência em desproveito da mulher: submissão bíblica, religiosa, social e jurídica - Bezerra , Luis Antônio Alves (2018)
This thesis aims at assessing violence to the detriment of women in the Old Testament, which served as a religious amalgam for her elimination in the social environment of male domination, but not before proceeding with an approach to Hebrew history, in addition to the contextualization of the ancient Hebrew codes : Covenant, Deuteronomy and Leviticus, with the intercalation and paradox of violence exercised against her in each of the Old Testament codices, which have been transfused into all societies, even the most modern, in the West. It contributed, therefore, the feminist historical oppression, by the patriarchal connotation biblical, religious and social for the enactment of laws that, notoriously, inhibited in the human genesis the devaluation by the feminine condition. Its recrudescence, in the social context, in Brazil needed to establish equality between the sexes, by the Federal Constitution of 1988 and specific punishment for gender violence, due to the publication of the Laws of Maria da Penha (Lei nº 11.340 / 2006), besides the Feminicide Law no. 13.104 / 2015), to reduce the existing androcentric intolerance in Brazilian society, still pending social re-signification, to reduce contempt, humiliation, monetization and domestic violence, so common in Brazilian homes.